1983
DOI: 10.1007/bf02619574
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymic in vitro isolation of perinatal islets of Langerhans

Abstract: We have developed a method to circumvent the use of exogenous proteolytic enzymes in the isolation of islets of Langerhans from the perinatal rodent pancreas. Advantage is taken of the propensity of fibroblastlike cells to attach and migrate on polystyrene at low-serum concentrations (5%). In contrast, at this serum level, rat islet epithelial cells tend not to adhere to the substrate. At 3 d of culture, islets are visible at the edges of the explants. With further fibroblast outgrowth the majority of islets a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…This effect on p-cell replication on the addition of exogenous insulin to neonatal rat pancreatic monolayer cultures has recently been reported. 19 Our studies also confirm the data of Hegre et al 20 on islet yield from the perinatal pancreas. These authors utilized a nonenzymatic method to isolate the islets and demonstrated that, compared with amounts from the fetal or mature rat pancreas, islet yield was higher in young postnatal pancreatic tissue and that day 5 of postnatal life yielded the most islets.…”
Section: Discussionsupporting
confidence: 92%
“…This effect on p-cell replication on the addition of exogenous insulin to neonatal rat pancreatic monolayer cultures has recently been reported. 19 Our studies also confirm the data of Hegre et al 20 on islet yield from the perinatal pancreas. These authors utilized a nonenzymatic method to isolate the islets and demonstrated that, compared with amounts from the fetal or mature rat pancreas, islet yield was higher in young postnatal pancreatic tissue and that day 5 of postnatal life yielded the most islets.…”
Section: Discussionsupporting
confidence: 92%
“…Islet Isolation and Culture-Islets were isolated and cultured by a modification of the method described (9). Pancreata were harvested from 5 to 10, 4-or 5-day-old neonatal rat pups and placed in 4 ml of Ham's F-12 medium containing 5% (v/v) fetal bovine serum, 100 IU/ml penicillin, and 100 g/ml streptomycin (culture medium).…”
Section: Methodsmentioning
confidence: 99%
“…Many procedures exist for the recovery of islets from the adult pancreas [22][23][24][25][26][27]. The scattered distribution of endocrine cells in the human fetal pancreas excludes standard islet isolation procedures [9].…”
Section: Discussionmentioning
confidence: 99%